Occurrence and Determination of Haloacetic Acids in Metro Manila Drinking Water - Rodriguez, Irene B.; Espino, Maria Pythias B. (Science Diliman: A Journal of Pure and Applied Sciences, 2010)
Haloacetic acids are found in chlorinated water with high organic matter content. An analytical method based on a US EPA method for measuring these compounds in water is described. The optimized method used diethyl ether as extraction solvent with sulphuric acid-methanol as esterification agent and subsequent detection by gas chromatography-electron capture detection. Evaluation of this method showed that it was linear in the concentration range of 10 to 150 µg L -1 and the method detection limits were from 17 to 57 µg L -1 . Although the method demonstrated low recoveries (16 to 43%), it is useful in the quantitative determination of monochloroacetic acid as well as the qualitative determination of other haloacetic acids in water. Drinking water samples taken from different areas in Metro Manila serviced by the local treatment plants were analysed using the method. Monochloroacetic acid, monobromoacetic acid, and bromochloroacetic acid were detected in these samples. Monochloroacetic acid was quantified and found in concentrations ranging from 19 to 157 µg L -1 . In most of the water samples, the concentration of monochloroacetic acid exceeded the US EPA maximum allowable total concentration of 60 µg L -1 for the five haloacetic acids (monochloro-, dichloro-, trichloro-, monobromo-, and dibromoacetic acids) in drinking water. This initial study established the occurrence of potentially harmful haloacetic acids in the local drinking water supplies.
Keywords: chlorination; haloacetic acids; disinfection by-products; drinking water